Negative Emotion Weakens the Degree of Self-Reference Effect: Evidence from ERPs - Fan, Wei; Zhong, Yiping; Li, Jin; Yang, Zilu; Zhan, Youlong; Cai, Ronghua; Fu, Xiaolan (Frontiers in Psychology, 2016)
We investigated the influence of negative emotion on the degree of self-reference effect using event-related potentials (ERPs). We presented emotional pictures and self-referential stimuli (stimuli that accelerate and improve processing and improve memory of information related to an individual’s self-concept) in sequence. Participants judged the color of the target stimulus (self-referential stimuli). ERP results showed that the target stimuli elicited larger P2 amplitudes under neutral conditions than under negative emotional conditions. Under neutral conditions, N2 amplitudes for highly self-relevant names (target stimulus) were smaller than those for any other names. Under negative emotional conditions, highly and moderately self-referential stimuli activated smaller N2 amplitudes. P3 amplitudes activated by self-referential processing under negative emotional conditions were smaller than neutral conditions. In the left and central sites, highly self-relevant names activated larger P3 amplitudes than any other names. But in the central sites, moderately self-relevant names activated larger P3 amplitudes than non-self-relevant names. The findings indicate that negative emotional processing could weaken the degree of self-reference effect.